The Interrelationship of Estrogen Receptor and GnRH in a Basal Vertebrate, the Sea Lamprey - Sower, Stacia A. (Frontiers in Endocrinology, 2011)
The hypothalamic-pituitary system is considered to be a vertebrate innovation and seminal event that emerged prior to or during the differentiation of the ancestral agnathans. Lampreys are the earliest evolved vertebrates for which there is a demonstrated neuroendocrine system. Lampreys have three hypothalamic GnRHs (lGnRH-I, -II, and –III) and two and possibly three pituitary GnRH receptors involved in mediating reproductive processes. Estradiol is considered to be a major reproductive steroid in both male and female lampreys. The purpose of this study was to investigate estrogen receptor (ER) expression in the lamprey brain in adult sea lampreys. Expression of ER mRNA was confirmed in the adult lamprey brain using RT-PCR. Using digoxigenin (DIG)-labeled probes, ER expression was shown to yield moderate, but distinct reaction products in specific neuronal nuclei of the lamprey brain, including the olfactory lobe, hypothalamus, habenular area, and hindbrain. Expression of ER in the hypothalamic area of the brain provides evidence of potential interaction between estradiol and GnRH(s), and is consistent with previous evidence showing estrogen feedback on GnRH in adult lamprey brain. Earlier studies have reported that there is a close distribution of GAD (GABA) and lamprey GnRH in the preoptic region in adult lampreys. The establishment of a direct estradiol-kisspeptin-GABA-GnRH interaction in lamprey has yet to be determined and will require future functional and co-localization studies. The phylogenetic position of lampreys as a basal vertebrate allows lampreys to be a basis for understanding the molecular evolution of the neuroendocrine system that arose in the vertebrates.